Tworzenie rzeczowników ekspresywnych w dialektach smoleńskich i w języku polskim - Gałant, Swietłana (Studia Rossica Posnaniensia, 2010)
Presently we experience favorable condition for comparative study of Smolensk region dialects and Polish language due to publishing of Smolensk region dialects vocabulary with a rich dialect contents. The paper will present a comparison of word formation structures of Smolensk region dialects and modern Polish language. Word formation comparison of expressive nouns, subjective assessment suffixes, word formation models typical for both Slavic languages and language-specific will be covered in necessary details.